Wirkmechanismen antidepressiver Pharmakotherapie: Gehirn und Psyche - Körper und Umwelt - Spangemacher, Moritz; Reinwald, Jonathan Rochus; Adolphi, Hana; Kärtner, Laura; Mertens, Lea Julia; Schmitz, Christian N.; Gründer, Gerhard (Der Nervenarzt, 2025)
Background Novel antidepressive substances are challenging the explanations for the mechanisms of action of traditional psychopharmacology. Objective What could be the shared effects of various antidepressants and in this context what role do extrapharmacological factors, such as the body and environment, play? Material and method The available literature on clinical and preclinical data for assumed combined active factors of serotonergic psychedelic drugs, (es)ketamine, monoaminergic antidepressants and zuranolone are presented and the influence of context factors on the individual mechanisms of action is discussed. Results There are many indications that classical and novel pharmacological approaches could share similar mechanisms of action in the treatment of depression. These mechanisms favor long-term neuroplasticity, which can trigger subsequent molecular cascades and vice versa. Furthermore, an improvement in the negative bias in emotional processing could be detected for most antidepressive substances. The influence of extrapharmacological factors appears to be necessary so that the biopsychological alterations can have an antidepressive effect. Conclusion Instead of attributing factors such as environment, body and social interaction to placebo effects, they should be tested as essential components of the antidepressive effect and considered in the clinical practice.
Online veröffentlicht: 16. Januar 2025
Gesehen am 30.06.2025